2022
DOI: 10.1002/app.52968
|View full text |Cite
|
Sign up to set email alerts
|

Structure, properties, and in vitro degradation behavior of biodegradable poly(L‐lactic acid)‐trimethylene carbonate‐glycolide terpolymer

Abstract: For biodegradable medical implants, it is critical to match the degradation rate of the material with the lesion healing rate of the tissue defect. Here, we report the synthesis of poly(L-lactic acid) (PLLA)-trimethylene carbonate (TMC)glycolide (GA) terpolymers with various monomer feeding ratios of L-lactide, TMC, and GA. The terpolymers were prepared through ring-opening polymerization with the purpose to improve degradation and mechanical properties of the terpolymers for biomedical applications. The influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Poor biological integration, low biocompatibility, and a high chance of fibrosis often hinder application of engineered scaffolds in vivo . Given the low elastic modulus of human myocardium during the diastole and systole cycles (10–300 kPa), an ideal elastomer for implantable patches should possess a similar Young’s modulus, as well as high elongation and tensile strength in order to support the contractile behavior of cardiac tissue. ,,, Implementation of cardiac patches with better physiological integration has raised a great interest toward restoring the functionality of the heart upon injury . Patches could be made of a combination of synthetic polymers and natural hydrogels. ,, A landmark study by Zimmermann et al demonstrated that the use of cardiac patches, made of heart cells incorporated in collagen I and Matrigel, on the epicardial surface of the heart can result in functional improvement post-MI .…”
Section: In Vitro and In Vivo Applications Of Soft Polyestersmentioning
confidence: 99%
“…Poor biological integration, low biocompatibility, and a high chance of fibrosis often hinder application of engineered scaffolds in vivo . Given the low elastic modulus of human myocardium during the diastole and systole cycles (10–300 kPa), an ideal elastomer for implantable patches should possess a similar Young’s modulus, as well as high elongation and tensile strength in order to support the contractile behavior of cardiac tissue. ,,, Implementation of cardiac patches with better physiological integration has raised a great interest toward restoring the functionality of the heart upon injury . Patches could be made of a combination of synthetic polymers and natural hydrogels. ,, A landmark study by Zimmermann et al demonstrated that the use of cardiac patches, made of heart cells incorporated in collagen I and Matrigel, on the epicardial surface of the heart can result in functional improvement post-MI .…”
Section: In Vitro and In Vivo Applications Of Soft Polyestersmentioning
confidence: 99%